Morphometric analysis of trianchoratus price & berry, 1966 (Monogenea: Heteronchocleidinae) from channa spp. (Osteichthyes: Channidae) of peninsular Malaysia - Tan, W.B.; Khang, T.F.; Lim, L.H.S. (National University of Singapore, 2010)
The morphometric data of anchors of 448 specimens belonging to four species of Trianchoratus Price & Berry, 1966, from Channa lucius (Cuvier) and C. striata (Bloch) were statistically analysed using principal components analysis (PCA) and Fisher's linear discriminant (LD) analysis. Both methods were able to differentiate the 448 specimens into four groups which correspond to the four species of Trianchoratus viz. T malayensis Lim, 1986, T pahangensis Lim, 1986, T longianchoratus Tan & Lim, 2009, and T ophicephali Lim, 1986, based on the over all size of the three developed anchors and the two main morphometric descriptors are the inner length and outer length of the dorsal anchor. PCA and one-way multivariate analysis of variance (MANOVA) of the individuals within each species indicated the presence of groups or intraspecific morphometric variants within T malayensis, T pahangensis and T ophicephali. There are indications of morphovariants within T longianchoratus, but more specimens are needed to verify the number of the morphometric variants. Preliminary analyses suggest that the intraspecific morphometric variants could be locality-dependent as in T malayensis and T ophicephati, and partially host-dependent as in T pahangensis. The distinguishing morphometric characters for the four Trianchoratus species and for each existing morphometric variants of the three species are presented.